Analisis Isi Pesan Dakwah K.H. Ahmad Dahlan pada Film Sang Pencerah - Abdul Muiz Sa'adih (STID DI AL-HIKMAH, 2015)
This study aims to analyze the da’wah message of K.H. Ahmad Dahlan contained in the film of Sang Pencerah. The film lasts one hundred and twelve minutes was written and directed by Hanung Bramantyo. The history background of this film is in the late 19th century that tells lunge Mohammed Dervish, which was then known as the KH Ahmad Dahlan. The methodology used is qualitative content analysis, the process of data collection by observation, interviews and a literature review. The contents of the message da’wah in the film include three categories: message of aqidah, worship and morals. The propagation method used by K.H. Ahmad Dahlan in preaching includes three ways: bil hikmah, bil mauidzah hasanah and mujadalah bi al-lati hiya ahsan.